Investigating a DHF Outbreak in Batuan Village, Gianyar - Lahari, Ni Luh Putu Sri; Putra, I Wayan Gede Artawan Eka; Septarini, Ni Wayan (Basic and Applied Nursing Research Journal, 2025)
Background: In March–April 2025, an unusual increase in Dengue Hemorrhagic Fever (DHF) cases was reported in Banjar Dentiyis, Batuan Village, Sukawati District, Gianyar, Bali. The case count rose from 8 in the previous year to 20 within two months, including one death. The sharp increase in incidence and mortality met the criteria for a Kejadian Luar Biasa (KLB), or outbreak, as defined by the Indonesian Ministry of Health. This investigation was conducted to characterize the outbreak, identify contributing risk factors, and evaluate the public health response. Objective: To determine the epidemiological profile and environmental risk factors associated with the DHF outbreak in Banjar Dentiyis and to provide recommendations for prevention and control. Methods: A descriptive cross-sectional investigation was carried out from April 4 to 30, 2025. Data collection included secondary surveillance data from Puskesmas Sukawati I and primary field investigations involving interviews, environmental inspections, and larval surveys. Cases were analyzed based on demographic characteristics, spatial distribution, temporal trends, and risk factors such as the presence of larvae and container density. Results: Twenty DHF cases and one death were confirmed, with the highest concentration (12 cases) in Gang Bunut, yielding an attack rate of 12.9% and a local CFR of 8.3%. Most patients were female (60%) and over the age of 15, although the highest attack rate (3.79%) occurred among children under 15. Clinical symptoms were consistent across cases, with all patients experiencing fever and most reporting headaches and nausea. Environmental assessment revealed mosquito larvae in 35% of case households, with bromeliad plants and uncovered containers serving as primary breeding sites. Fogging and vector control interventions were delayed and did not follow recommended intervals. Conclusion: The outbreak in Banjar Dentiyis highlights the need for timely response, routine vector surveillance, and sustained community engagement. Delays in fogging and inadequate container management contributed to the persistence of transmission. Strengthened preventive measures, improved health literacy, and adherence to dengue control protocols are critical to mitigating future outbreaks.